2011
DOI: 10.1371/journal.pone.0025904
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Presentation, Management, and In-Hospital Outcomes for Patients with AMI in a Lower-Middle Income Country: Evidence from Egypt

Abstract: BackgroundMany studies in high-income countries have investigated gender differences in the care and outcomes of patients hospitalized with acute myocardial infarction (AMI). However, little evidence exists on gender differences among patients with AMI in lower-middle-income countries, where the proportion deaths stemming from cardiovascular disease is projected to increase dramatically. This study examines gender differences in patients in the lower-middle-income country of Egypt to determine if female patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 22 publications
12
30
0
Order By: Relevance
“…46% of our female patients were found to be hypertensive as compared to 28% of males which is similar to the studies from West where hypertension on an average was 25% more common in females [19,20]. The declining oestrogen levels increased plasma rennin activity due to up-regulated rennin-angiotensin system, increased salt sensitivity with sympathetic activity with menopause are few factors which lead to a steep rise in blood pressure in peri-menopausal and post menopausal women [21].…”
Section: Discussionsupporting
confidence: 84%
“…46% of our female patients were found to be hypertensive as compared to 28% of males which is similar to the studies from West where hypertension on an average was 25% more common in females [19,20]. The declining oestrogen levels increased plasma rennin activity due to up-regulated rennin-angiotensin system, increased salt sensitivity with sympathetic activity with menopause are few factors which lead to a steep rise in blood pressure in peri-menopausal and post menopausal women [21].…”
Section: Discussionsupporting
confidence: 84%
“…The application of the randomization process in the current study was successful as shown by the absence of any significant differences in the socio-demographic and medical characteristics of the patients in the study and control groups. The percentage of women in both groups was slightly higher, which is in congruence with the known gender distribution, with higher prevalence among females [28]. There was also a high percentage of positive family history in the two groups, which goes in line with the findings of a recent study in Minia Governorate [29].…”
Section: Itemssupporting
confidence: 88%
“…Some studies showed that the clinical management of men and women after AMI was very similar (22) , but other studies have shown prominent differences (16) . In setting of hospitalization for CAD, women were found to have a higher incidence of CAD risk factors like diabetes and systemic hypertension, were less likely to be smokers (14) but they presented more frequently with heart failure due to diastolic dysfunction which may explain their higher unadjusted in-hospital mortality rates in AMI (15, 16 & 17) .…”
Section: Discussionmentioning
confidence: 99%
“…A study using data from the Global Registry for Acute Coronary Events (GRACE) that examined 43,393 patients (14,180 women and 29,213 men) with acute coronary syndromes from 14 countries observed similar patterns. In the GRACE study, women with ACS were more likely to be older, have higher rates of hypertension, diabetes, whereas men were more likely to smoke (16) . Limitations of our study were: a) retrospective b) nonrandomized c) conducted in a single center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation